Bilateral Gonadal Cysts and Late Diagnosis of Androgen Insensitivity Syndrome Treated by Laparoscopic Gonadectomy - D. Tourlakis; J. Schnabel; N. Fersis (Case Reports in Obstetrics and Gynecology)
Background. Complete androgen insensitivity syndrome is a rare syndrome in which the uterus is absent and testes rather than ovaries are present. Patients usually visit a gynecologist due to primary amenorrhea. Case. A forty-eight-year-old woman with lower abdominal pain and anamnesis of uterus agenesis was operated on due to bilateral cystic masses. A 5 × 3 × 1.2 cm left adnexal cyst revealed the presence of a serous cyst with a hypoplastic ductus deferens. A smaller cyst of the right adnexa revealed immature testis tissue with Leydig-cell hyperplasia. After karyotype and hormonal examinations, laparoscopic gonadectomy was performed. Conclusion. Attention should be paid in all cyst-removing operations in cases of uterus agenesis, due to the high incidence of malignancy. Not of less importance is the issue of informing the patient in the most appropriate way.